2018
DOI: 10.1021/acsami.7b14733
|View full text |Cite
|
Sign up to set email alerts
|

Tungsten-Assisted Phase Tuning of Molybdenum Carbide for Efficient Electrocatalytic Hydrogen Evolution

Abstract: Phase tuning during crystal phase transformation is an important but challenging step toward the development of effective hydrogen evolution reaction (HER) catalysts. Herein, we report on a feasible approach to achieve effective polycrystalline molybdenum carbides during transformation from α-phase to β-phase through the regulation of additive (tungsten) amount. Benefiting from the optimal Mo-C bond lengths and abundant active sites, molybdenum carbide prepared with a moderate addition of tungsten enhanced ele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
18
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(18 citation statements)
references
References 54 publications
0
18
0
Order By: Relevance
“…Electrochemical water splitting is widely considered to be a critical step for efficient renewable energy conversion via the hydrogen evolution reaction (HER) and oxygen evolution reaction (OER) . Nevertheless, the OER, which involves four proton‐couple electron transfer steps, has a high activation barrier due to the sluggish reaction kinetics .…”
Section: Introductionmentioning
confidence: 99%
“…Electrochemical water splitting is widely considered to be a critical step for efficient renewable energy conversion via the hydrogen evolution reaction (HER) and oxygen evolution reaction (OER) . Nevertheless, the OER, which involves four proton‐couple electron transfer steps, has a high activation barrier due to the sluggish reaction kinetics .…”
Section: Introductionmentioning
confidence: 99%
“…27 Furthermore, during the carbide synthesis process, the generation of surface contaminants blocks the active sites and cavities, resulting in the degradation of electrocatalytic activities. 28 In general, carbides are typically prepared by solid-solid or gas-solid reactions to achieve high surface area, namely, direct pyrolysis of metal carbonyl compounds, or reaction of metal/metal oxides with a C source. 22 Consequently, the aggregation and/or excessive growth of TMCs during pyrolysis at relatively high temperatures leads to a reduction in the active sites and electrocatalytic activities for electrochemical reactions.…”
Section: Introductionmentioning
confidence: 99%
“…Molybdenum carbide is one of the most widely studied transition metal carbide based catalysts for HER 9,[12][13][14][15] . Vrubel et al showed that the activity of bulk Mo2C is relatively independent of pH, with overpotentials at 10 mA/cm 2 , η, at pH 0 and 14 of 209 mV and 191 mV 9 , respectively.…”
Section: Introductionmentioning
confidence: 99%